2019
DOI: 10.1101/723809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Residual feed intake in dairy ewes: an evidence of intraflock variability

Abstract: 6 7 8 a Abstract 9 This study examined the intraflock variability of feed efficiency in dairy ewes, through 1 0 monitoring residual feed intakes (RFI). Primiparous lactating ewes (n=43; 57.7±0.91 kg body 1 1 weight [BW] at lambing), representative of a French Lacaune dairy flock, were allocated in an 1 2 equilibrated 2 × 2 factorial design experiment, lasting for 63 days during mid-lactation and 1 3 combining 2 litter sizes (singletons, SING or twins, TWIN) and 2 daily milking frequencies (once, 1 4 ONE or twi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the last years, an increasing number of researchers in ruminant nutrition have turned their efforts towards prioritizing an improvement in feed efficiency over production level [ 17 , 18 , 19 ]. Although there is still very little information on this topic, particularly in dairy ewes [ 20 , 21 ], a recent study has suggested a relationship between feed efficiency and lipid metabolism in the ovine, with certain milk FA being potential biomarkers of this trait (e.g., saturated C4–C14 FA, saturated C4–C14 fatty acids/ cis -9 18:1 ratio, or C20–22 n-6 polyunsaturated FA) [ 22 ]. Thus, because diet composition has a great influence on the efficiency of feed utilization [ 19 , 23 , 24 ], re-evaluation of the use of lipid supplements aimed at improving milk FA composition is required to examine their effects on metrics and biomarkers of feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, an increasing number of researchers in ruminant nutrition have turned their efforts towards prioritizing an improvement in feed efficiency over production level [ 17 , 18 , 19 ]. Although there is still very little information on this topic, particularly in dairy ewes [ 20 , 21 ], a recent study has suggested a relationship between feed efficiency and lipid metabolism in the ovine, with certain milk FA being potential biomarkers of this trait (e.g., saturated C4–C14 FA, saturated C4–C14 fatty acids/ cis -9 18:1 ratio, or C20–22 n-6 polyunsaturated FA) [ 22 ]. Thus, because diet composition has a great influence on the efficiency of feed utilization [ 19 , 23 , 24 ], re-evaluation of the use of lipid supplements aimed at improving milk FA composition is required to examine their effects on metrics and biomarkers of feed efficiency.…”
Section: Introductionmentioning
confidence: 99%